2017
DOI: 10.1016/j.hjb.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Developments on Pathogenicity, Molecular Virulence, Epidemiology and Clinical Symptoms of Current Middle East Respiratory Syndrome Coronavirus (MERS-CoV)

Abstract: a b s t r a c tMiddle East respiratory syndrome coronavirus (MERS-CoV) is a recently reported virus that is associated with severe, life threatening and rapidly spreading primarily respiratory illness called the Middle East respiratory syndrome. MERS-CoV possesses a unique positive-sense single-stranded RNA and can undergo rapid mutation in the viral genome. This results in antigenic switching and genetic variation, finally leading to the emergence of novel and new MERS-CoV subtypes which are uncontrollable by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
(12 reference statements)
0
12
0
2
Order By: Relevance
“…Ex vivo study of human lung cell lines shows that the induction of cytokines was suppressed during MERS-CoV infection [ 133 ]. Nevertheless, another study on respiratory epithelial cell line Calu-3 cells demonstrated that there was a delay in the induction or activation of proinflammatory cytokines such as IL-1β, IL-8 and IL-6 [ 134 ]. Expression of antiviral cytokines such as IFN-α and IFN-β was not triggered by viruses in the body [ 121 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Ex vivo study of human lung cell lines shows that the induction of cytokines was suppressed during MERS-CoV infection [ 133 ]. Nevertheless, another study on respiratory epithelial cell line Calu-3 cells demonstrated that there was a delay in the induction or activation of proinflammatory cytokines such as IL-1β, IL-8 and IL-6 [ 134 ]. Expression of antiviral cytokines such as IFN-α and IFN-β was not triggered by viruses in the body [ 121 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Although the mortality rate of the SARS-CoV-2 virus is low, this novel coronavirus (COVID- 19) is one of the most infectious diseases affecting our planet in the past decades. This virus was first spotted in Wuhan, China, and has now globally spread to over 190 countries, infecting more than 400,000 people and more than 15,000 deaths (2,3). Governments and health organizations of the world are constantly working day and night to combat the disease, but it has so far proved to be a major hur-dle.…”
Section: Contextmentioning
confidence: 99%
“…Selesma ini dapat disebabkan oleh berbagai jenis virus yang biasa menginfeksi saluran pernapasan [37][38] [39]. Ada banyak jenis virus yang dapat menyebabkan timbulnya gejala selesma [40], seperti Rhinovirus, Coronavirus, Influenza, Adenovirus, Enterovirus, Metapneumovirus dan masih banyak lagi virus lainnya yang jumlahnya mencapai kurang lebih 200 virus [41][42] [43]. Penyebab tersering selesma adalah Rhinoviru [44] [45].…”
Section: Pendahuluanunclassified